2011
DOI: 10.1021/jp1118212
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Large Magnetic Moments in Icosahedral Pb Nanoparticles

Abstract: ARTICLEtransfer between the surface and core regions can result in a redistribution of conduction electrons that alters the available conduction electron density for Cooper pairing. Second, the internal magnetic field generated by the magnetic moments in the particle can also suppress the formations of Cooper pairs. Unfortunately, it is not feasible to draw a conclusion on the importance of each factor in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We consider binary metallic systems which phase diagrams are characterized by large miscibility gaps, with a weak tendency to intermixing. By means of atomistic and density-functional theory (DFT) calculations, we show that concentrations of the order of 1–2% of small impurities in a matrix of larger atoms cause a transition from crystalline bulk-like structures to noncrystalline icosahedral (Ih) structures. Ih nanoparticles are of special interest because they can present enhanced catalytic and magnetic properties. As a counterproof we show that also the opposite transition, from icosahedra to crystalline bulk-like structures, can be induced by including impurities whose atomic size is larger than the size of the atoms of the matrix. These behaviors are a specific property of nanoscale objects, since the inclusion of the same percentage of impurities in bulk crystals would not produce any relevant structural change.…”
mentioning
confidence: 81%
“…We consider binary metallic systems which phase diagrams are characterized by large miscibility gaps, with a weak tendency to intermixing. By means of atomistic and density-functional theory (DFT) calculations, we show that concentrations of the order of 1–2% of small impurities in a matrix of larger atoms cause a transition from crystalline bulk-like structures to noncrystalline icosahedral (Ih) structures. Ih nanoparticles are of special interest because they can present enhanced catalytic and magnetic properties. As a counterproof we show that also the opposite transition, from icosahedra to crystalline bulk-like structures, can be induced by including impurities whose atomic size is larger than the size of the atoms of the matrix. These behaviors are a specific property of nanoscale objects, since the inclusion of the same percentage of impurities in bulk crystals would not produce any relevant structural change.…”
mentioning
confidence: 81%
“…A particularly fascinating example of size- and shape-dependent nanocrystal properties can be found for metal nanocrystals that exhibit multiply twinned structures, such as decahedra and icosahedra. There has been a longstanding and continuing interest in these nanostructures–particularly in their growth mechanisms and in the strain associated with the twins. Recent studies have shown that these nanoparticles can have unique and beneficial catalytic, mechanical, optical, and magnetic properties. In efforts to understand and tailor these properties, a detailed understanding of the structures and inherent strain fields in these nanocrystals would be useful.…”
mentioning
confidence: 99%
“…For instance, gold and silver icosahedra were found to have much higher electrocatalytic activity than their sphere-like analogues. , The Ic nanoparticles are also of great interest in magnetic applications. Compared to their single crystal morphologies, large magnetic moments were observed in Ic nanoparticles and surprising oxidation resistance has been observed in Ic FePt nanoparticles, , an important consideration for obtaining high signal-to-noise ratio in magnetoresistive sensors . The Dh-shaped nanoparticles also offer unique opportunities for improved performance in plasmonic, , optical, and catalytic applications …”
mentioning
confidence: 99%